Uji Aktivitas Penyembuhan Luka Bakar Salep Ekstrak Etanol Buah Parijoto (Medinilla Speciose) pada Punggung Kelinci - Harimuddin; Saraswati, Maulita; Supriyanto (Yayasan Citra Dharma Cindekia, 2024)
Medinilla speciosa contains flavonoids, saponins, tannins and alkaloids which have activity as anti-biofilm, antibacterial, antioxidant, antiseptic and play a role in tissue regeneration in the wound healing process. This study aimed to prove the activity of M. speciosa fruit made in ointment and its optimal concentration in healing second degree burns. This research was an experimental study in the laboratory to analyze the secondary metabolite content of flavonoids, saponins, tannins, alkaloids, and the burn wound healing activity of M. speciosa ethanol. This research used 3 rabbits as test animals and created 5 standardized wound locations on the rabbits' backs. Wound standardization was carried out using a heated 2 cm diameter metal plate. At 5 wound locations, each was given a test ointment preparation with a concentration of 0.075%, 0.15%, 0.30%, ointment base (negative control), and mebo ointment (positive control) for 10 days with the parameter measured being the diameter of the wound. The physical properties of the ointment include organoleptic tests, homogeneity, viscosity, spreadability and adhesiveness. The data obtained was analyzed statistically using analysis of variance. The result of this research were the all concentrations of M. speciosa fruit ethanol extract ointment showed a burn healing effect. The best wound healing based on statistical data results was shown by M. speciosa fruit extract ointment with a concentration of 0.30% with an average percentage of wound diameter closure that was the same as the positive control, namely 100% on day 10.